Sustainable leadership, organizational trust on job satisfaction: empirical evidence from higher education institutions in Syria - Dalati, Serene; Raudeliūnienė, Jurgita; Davidavičienė, Vida (Business, Management and Economics Engineering, 2017)
This research develops a theoretical model of sustainable leadership, organizational trust and satisfaction at work in higher education environment in Syria. The model assesses staff perception of outstanding leadership behaviors and examines its relationship with perceived organizational trust in the field of higher education institutions in Syria. This research examines a conceptual framework identifying outstanding leadership styles and behaviors which are associated with sustainable leadership, organisational trust identified by members’ trust in their coworkers, and job satisfaction at an institutional level. The research methodology applied in this research develops a quantitative approach through application of questionnaire survey. To measure the dimensionality of scale factors an exploratory factor analysis is conducted. Reliability analysis is performed, Cronbach alpha test indicates that the research scales are internally consistent. The sample of the study employed a convenience sample from higher education institutions. The managerial implication of the research study recommends application and adoption of sustainable leadership behaviors among functional, mid and senior levels of managers and academics in management positions in higher education institutions. The limitation of research is mainly indicated in the sample size and measurement scales of sustainable leadership, organizational trust and job satisfaction.